EFFECTIVENESS OF THE USE OF MOODLE-ECLASS LEARNING MEDIA IN IPS LEARNING IN SATYA WACANA CHRISTIAN MIDDLE SCHOOL - pamuttu, piter -; Widiarto, Tri; Sunardi, Sunardi (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2021)
This study aims to discuss the effectiveness of using the Moodle-Eclass application in the social studies learning process at Satya Wacana Christian Middle School. With the government's recommendation to conduct distance learning due to the Covid-19 outbreak, every school is obliged to provide application services that are used for the learning process, the use of moodle-Eclass at Satya Wacana Christian Middle School is to make it easier for students andteachers to manage learning.The use of Moodle-Eclass itself at Satya Wacana Christian Middle School shows the effectiveness of its use when viewed from its users which are more trusted by the school in managing student test exams, distributing materials, announcements and as a medium for collecting assignments. One of the problems found was that the interface was difficult for beginners to use, so a course or tutorial was needed to use it. but this application has the advantage that it has many educational support features and the use of test media that is easy for teachers to input school test questions.